First Record of Kaloula assamensis Das Etal. (2004) (Microhylidae) from Bihar State, India, with Notes on its Distribution - Deuti, Kaushik; Sethy, P. G. S.; Ray, Sukumar; Chattopadhyay, Mrityunjay (Journal of the Bombay Natural History Society (JBNHS), 2012)
No Abstract.